2017
DOI: 10.1177/1059840517704964
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Habits and Nighttime Texting Among Adolescents

Abstract: The aim of this study was to examine sleep habits (i.e., bedtimes and rising times) and their association with nighttime text messaging in 15-to 17-year-old adolescents. This cross-sectional study analyzed data from a web-based survey of adolescent students attending secondary schools in southern Sweden (N ¼ 278, 50% female). Less than 8 hr of time in bed during school nights was significantly associated with more sleep difficulties, wake time variability on school days and weekends, daytime tiredness, and les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 43 publications
5
30
0
1
Order By: Relevance
“…The adolescents described their technology use as having to be connected around the clock, making it difficult to stop technology use. Technology use was a common reason for sleeping difficulties in this study which is in line with research by Hale and Guan and Garmy and Ward , which determined the links between technology use and sleeping difficulties in the form of delayed timing and shortened sleep duration. Perhaps the adolescents’ technology use in this study was also present in the categories of stress, poor sleep habits and existential thoughts, even though the adolescents did not express this.…”
Section: Discussionsupporting
confidence: 89%
“…The adolescents described their technology use as having to be connected around the clock, making it difficult to stop technology use. Technology use was a common reason for sleeping difficulties in this study which is in line with research by Hale and Guan and Garmy and Ward , which determined the links between technology use and sleeping difficulties in the form of delayed timing and shortened sleep duration. Perhaps the adolescents’ technology use in this study was also present in the categories of stress, poor sleep habits and existential thoughts, even though the adolescents did not express this.…”
Section: Discussionsupporting
confidence: 89%
“…Nighttime sleep and daytime functioning of adolescents are affected by technology use before sleep (Johansson et al, 2016). Similar studies have reported how nighttime texting habits are associated with disrupted sleep (Garmy and Ward, 2018) and that screen time (television and computer) is associated with sleep behavior (Garmy et al, 2012b) among young people.…”
Section: Discussionmentioning
confidence: 72%
“…In cross-sectional studies with children, as well as with adults, bedtime mobile phone use (in the broad definition, above) was associated with later bedtimes [16,22,31,82,85,88,93,223,263], longer sleep onset latency [53,79,112,223,293], shorter sleep duration [14,15,22,36,71,82,86,148,161,202,210], insomnia or sleep problems [5,14,79,85,97,144,199,202,205,235,269,293], reduced sleep quality or sleep efficiency [5,32,53,71,79,82,83,167,202,205], and reduced daytime functioning or tiredness [79,86,93,112,121,202,223,242,248,277,293]. In one study, keeping the phone close, rather than placing the phone at a distance from the bed, was associated with less sleep problems [235].…”
Section: Resultsmentioning
confidence: 99%